Bombyx mori ABC transporter C2 structures responsible for the receptor function of Bacillus thuringiensis Cry1Aa toxin. (December 2017) - Tanaka, Shiho; Endo, Haruka; Adegawa, Satomi; Iizuka, Ami; Imamura, Kazuhiro; Kikuta, Shingo; Sato, Ryoichi
Abstract: Because Bombyx mori ABC transporter C2 (BmABCC2) has 1000-fold higher potential than B. mori cadherin-like protein as a receptor for Bacillus thuringiensis Cry1Aa toxin (Tanaka et al., 2013), the gate-opening ability of the latent pore under six extracellular loops (ECLs) of BmABCC2 was expected to be the reason for its higher potential (Heckel, 2012). In this study, cell swelling assays in Sf9 cells showed that BmABCC2 mutants lacking substrate-excreting activity retained receptor activity, indicating that the gate-opening activity of BmABCC2 is not responsible for Cry1Aa toxicity. The analysis of 29 BmABCC2 mutants demonstrated that 770 DYWL 773 of ECL 4 comprise a putative binding site to Cry1Aa. This suggests that specific toxicity of Cry1Aa toxin to a restricted range of lepidopteran insects is dependent on conservation and variation in the amino acid residues around 770 DYWL 773 of ECL 4 in the ABCC2. Graphical abstract: Dispensable (strip) and indispensable (red) structures for Cry1Aa-receptor function of BmABCC2. Highlights: The gating activity of ABCC2 is not required for function as Cry1A receptor. 770 DYWL 773 region in ECL 4 is involved in Cry1A binding. BmABCC2 excretes Ca 2+ indicator, X-Rhod-1 from cells.